Occupational injuries sustained by caregivers in geriatric care homes of Kathmandu valley - Mahto, Prakash Kumar; Gautam, Bhupal; Joshi, Sunil Kumar (International Journal of Occupational Safety and Health, 2019)
Background: Ageing is an inevitable process. The population of elderly is increasing in Nepal. Caring of elderly at geriatric care homes is becoming popular. Caregivers take care of the elderly in the geriatric care homes. Occupational injuries are very common and no study has been done to document the injuries sustained by caregivers working in geriatric care homes in Nepal. This study has been conducted to determine the prevalence of work related musculoskeletal disorders and the injuries sustained among care givers working in geriatric care homes in Nepal. Methods: This is a descriptive cross-sectional study design. A convenience sample of 41 caregivers among geriatric care homes in Kathmandu valley aged between 20-45 years were included in the study. The Nordic musculoskeletal questionnaire was adapted to measure Musculoskeletal Disorders in the study population. Descriptive analysis of data was done. Type of injury was classified and their consequences observed. Results: Caregivers (n=41) reported work related musculoskeletal disorders in six areas of the questionnaire: Neck 4 (9.75 %), Shoulder 8(19.5%), Elbow 4(9.75%), Low back 22(53.65%), Knee 5(12.19%) and ankle 3(7.31%). Common types of injuries sustained were muscle strain, ligament sprain, joint pain, hernia etc. In most of the cases, caregivers had to take interventions like taking medications, exercises, rest while some were able to get away with minor symptoms. Conclusion: The incidence of occupational injuries among caregivers is high. The existing training programs are not enough. A revision of the course work for training of caregivers is necessary